PENGEMBANGAN PERANGKAT BEL SEKOLAH OTOMATIS DENGAN MICROCONTROLLER ARDUINO UNO BERBASIS INTERNET of THING (IoT) - Mudhoffar, Ghozy Ridho; Partono, Partono; Prihandono, Eko (JURNAL FIRNAS, 2022)
Abstract: The problem of undisciplined use of time can affect a person's success. A student is required to be disciplined, especially time discipline. The discipline of a student's time in school is usually marked and regulated by the school bell. The ringing of the bell in most schools still uses manual, so sometimes errors still occur, such as late ringing it. Then an automatic school bell was made that is integrated with electronic components to increase interest in helping students be disciplined. An automatic school bell is a tool that combines Arduino Uno with several other components so that the tool can sound automatically. The automatic school bell can also be used as a learning resource for physics. Developing this automatic school bell is a source of learning physics in electromagnetic wave material and digital technology and can help improve student discipline. This research method uses the (R&D) method with the ADDIE model. Research data was obtained from the results of expert validation and user responses. The validation results by two experts on media aspects obtained an average percentage of 96.25% with the criteria of "Very Eligible," and the results of validation by three experts on material aspects obtained a percentage of 91.03% with the criteria of "Very Eligible." then the results of the practicality of using the school bell automatically get an average percentage of 91.2% with the "Very Practical" CriteriaKeywords: Development, automatic school bell, Physics Learning Resources